Are we underusing peripheral parenteral nutrition? A 5‐year retrospective review of inpatient parenteral nutrition practices. (21st August 2022) - van der Walt, Ashley; Watt, Amanda; Kaushik, Vishal; Osland, Emma
Abstract: Background: Peripheral parenteral nutrition (PPN) represents an alternative option to central parenteral nutrition (CPN) for patients requiring short‐term parenteral nutrition (PN). We hypothesized that the use of PPN could be increased in certain patient cohorts referred for PN in our facility. Methods: A retrospective observational study investigating the clinical characteristics of patients receiving PN under the nutrition support team over a 5‐year period was undertaken. Patients who received PPN were reviewed descriptively. Of the patients who received CPN, representative samples were grouped into those who received PN for ≤7 or >7–28 days ( n = 100 each, randomly assigned). Clinical characteristics considered included indication, duration and referring team for PN, and nutrition status. Descriptive statistics and binary logistic regression model for predictors of PN duration of ≤7 or >7–28 days were derived. Results: Only four patients received PPN for a median of 4 days, most of whom required this route because of loss of central venous access for CPN. A high proportion of patients with no enteral access received CPN for ≤7 days, whereas the majority of patients with malabsorption required >7–28 days of CPN. Being referred for PN following upper gastrointestinal surgery increased the likelihood of CPN use for >7 days (relative risk, 5.7; 95% CI, 1.7–18.9; P = 0.004). Conclusion: Within our service, PN referrals for no enteral access may represent a group in whom PPN could be used in the first instance; those referred with an indication of malabsorption or following upper gastrointestinal surgery may benefit from early commencement of CPN.